PENGARUH VARIASI JUMLAH DAN JARAK ANTAR LAPIS GEOTEKSTIL TERHADAP DAYA DUKUNG DAN PENURUNAN PONDASI MENERUS PADA TANAH PASIR POORLY GRADED - ., Suroso; ., Harimurti; Wijaya, Gresi Dadik (Jurnal Mahasiswa Jurusan Teknik Sipil, 2014)
The damages of the buildings construction such as of buildings wall cracks caused by shear failure on the decrease excess. The main problem on the poorly graded sand  is a high decrease and low soil bearing capacity when given the imposition on it. A way to increase the bearing capacity can be reached by administration of reinforcement. The used reinforcement system is by installing geotextile geocomposite. The geotextile function is as the reinforcement soil where geotextile interacts with soil of friction or adhesion force to resist attractive force, so that the soil bearing capacity can be increased. This study used a variation on the distance between the reinforcement 0.2B, 0.3B, and 0.4B as well as variations in the amount of reinforcement that is one, two and three. The results of the installation of geotextile in this study indicates that the has increased bearing capacity models. Where an increase in the maximum bearing capacity occurs when the distance between the number of layers of reinforcement 0.2B and the others. Based on this test it can be concluded that the closer the distance between the reinforcement and the bigger number of layers of reinforcement, the bigger bearing capacity. Keywords : bearing capacity, decrease, geotextile-geocomposite, distance between the reinforcement, amount of reinforcement, continuous foundation.